Performance of experimental approach embankments at Salt Fork river bridges on U.S. 177 (FHWA-97-04) 2195 - (:unkn) unknown (My University, 1997)
In an effort to address the bump at the endˆ of the bridge problem, ODOT has undertaken an experimental construction research project to evaluate five different approach embankment construction methods. The research is being conducted at a relocation project in which three new bridges are being constructed to relocate a two-mile section of U.S. 177 north of Stillwater, Oklahoma. Five of the six approach embankments are approximately the same height and the foundation soils are relatively uniform, consisting of fine to medium dense sands. Materials and construction methods used for the five approach embankments in the study include: unclassified borrow placed by contractor's discretion (i.e., equipment)-this serves as the control for the research study; geotextile reinforced approach embankment using a nonwoven geotextile and granular backfill (i.e., concrete sand); controlled low strength material; dynamically compacted granular backfill; and flooded and vibrated granular backfill. During and following construction, all five approach embankments and. bridge abutments were instrumented to evaluate the performance of the approach embankments and interaction with the abutment walls. Specific instruments and the parameters they monitored included: total pressure cells on the back of the abutment walls to monitor lateral earth pressures caused by the approach embankments; amplified liquid settlement gages beneath the approach embankments to monitor settlement; inclinometer casings with telescoping couplings to monitor lateral displacement and settlement within the approach embankment and foundation materials; piezometers to monitor pore water pressures; and surface survey points to monitor total surface movement. In terms of settlement, the flooded and vibrated granular backfill appears to be performing the best. Lateral earth pressure values are closest to the predicted values for the geotextile reinforced backfill. The CLSM is performing well with respect to settlement. The dynamically compacted granular backfill embankment has the highest amount of settlement. The least expensive embankment construction was the control section which had a total cost of $1500. The most expensive was the geotextile reinforced backfill at $25,000. The remaining embankments cost in the range of $14,500 to $16,000.
Keywords: Settlement; approach embankments; lateral earth pressures; bridge performance instrumentation; embankment construction